Field-controlled ultrafast magnetization dynamics in two-dimensional nanoscale ferromagnetic antidot arrays - De, Anulekha; Mondal, Sucheta; Sahoo, Sourav; Barman, Saswati; Otani, Yoshichika; Mitra, Rajib Kumar; Barman, Anjan (Beilstein Journal of Nanotechnology, 2018)
Ferromagnetic antidot arrays have emerged as a system of tremendous interest due to their interesting spin configuration and dynamics as well as their potential applications in magnetic storage, memory, logic, communications and sensing devices. Here, we report experimental and numerical investigation of ultrafast magnetization dynamics in a new type of antidot lattice in the form of triangular-shaped Ni80Fe20 antidots arranged in a hexagonal array. Time-resolved magneto-optical Kerr effect and micromagnetic simulations have been exploited to study the magnetization precession and spin-wave modes of the antidot lattice with varying lattice constant and in-plane orientation of the bias-magnetic field. A remarkable variation in the spin-wave modes with the orientation of in-plane bias magnetic field is found to be associated with the conversion of extended spin-wave modes to quantized ones and vice versa. The lattice constant also influences this variation in spin-wave spectra and spin-wave mode profiles. These observations are important for potential applications of the antidot lattices with triangular holes in future magnonic and spintronic devices.
Keywords: ferromagnetic antidot lattice; magnonic crystal; micromagnetic simulations; spin-wave modes; time-resolved magneto-optical Kerr effect

(untitled) - Kruglyak, V. V.; Demokritov, S. O.; Grundler, D. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Lenk, B.; Ulrichs, H.; Garbs, F.; Münzenberg, M. (Phys. Rep., 2011)

(untitled) - Jung, S.; Ketterson, J. B.; Chandrasekhar, V. (Phys. Rev. B, 2002)

(untitled) - Rana, B.; Kumar, D.; Barman, S.; Pal, S.; Fukuma, Y.; Otani, Y.; Barman, A. (ACS Nano, 2011)

(untitled) - Pal, S.; Saha, S.; Kamalakar, M. V.; Barman, A. (Nano Res., 2016)

(untitled) - Wang, C. C.; Adeyeye, A. O.; Singh, N. (Nanotechnology, 2006)

(untitled) - Neusser, S.; Botters, B.; Becherer, M.; Schmitt-Landsiedel, D.; Grundler, D. (Appl. Phys. Lett., 2008)

(untitled) - Neusser, S.; Duerr, G.; Bauer, H. G.; Tacchi, S.; Madami, M.; Woltersdorf, G.; Gubbiotti, G.; Back, C. H.; Grundler, D. (Phys. Rev. Lett., 2010)

(untitled) - Ctistis, G.; Papaioannou, E.; Patoka, P.; Gutek, J.; Fumagalli, J.; Giersig, P. (Nano Lett., 2009)

(untitled) - Torres, L.; Lopez-Diaz, L.; Alejos, O. (J. Appl. Phys., 2000)

(untitled) - Sushruth, M.; Ding, J.; Duczynski, J.; Woodward, R. C.; Begley, R. A.; Fangohr, H.; Fuller, R. O.; Adeyeye, A. O.; Kostylev, M.; Metaxas, P. J. (Phys. Rev. Appl., 2016)

(untitled) - Kłos, J. W.; Kumar, D.; Romero-Vivas, J.; Fangohr, H.; Franchin, M.; Krawczyk, M.; Barman, A. (Phys. Rev. B, 2012)

(untitled) - Kłos, J. W.; Kumar, D.; Krawczyk, M.; Barman, A. (Sci. Rep., 2013)

(untitled) - Semenova, E. K.; Berkova, D. V. (J. Appl. Phys., 2013)

(untitled) - Madami, M.; Gubbiotti, G.; Tacchi, S.; Carlotti, G.; Jain, S. (Physica B, 2014)

(untitled) - Schneider, T.; Langer, M.; Alekhina, J.; Kowalska, E.; Oelschlägel, A.; Semisalova, A.; Neudert, A.; Lenz, K.; Potzger, K.; Kostylev, M. P.; Fassbender, J.; Adeyeye, A. O.; et al. (Sci. Rep., 2017)

(untitled) - Torresa, L.; López-Dı́az, L.; Alejos, O.; Iñigues, J. (J. Appl. Phys., 1999)

(untitled) - Deshpande, N. G.; Seo, M. S.; Jin, X. R.; Lee, S. J.; Lee, Y. P.; Rhee, J. Y.; Kim, K. W. (Appl. Phys. Lett., 2010)

(untitled) - McPhail, S.; Grtler, C. M.; Shilton, J. M.; Curson, N. J.; Bland, J. A. C. (Phys. Rev. B, 2005)

(untitled) - Mandal, R.; Barman, S.; Saha, S.; Otani, Y.; Barman, A. (J. Appl. Phys., 2015)

(untitled) - Tacchi, S.; Madami, M.; Gubbiotti, G.; Carlotti, G.; Adeyeye, A. O.; Neusser, S.; Botters, B.; Grundler, D. (IEEE Trans. Magn., 2010)

(untitled) - Ulrichs, H.; Lenk, B.; Münzenberg, M. (Appl. Phys. Lett., 2010)

(untitled) - Pal, S.; Klos, J. W.; Das, K.; Hellwig, O.; Gruszecki, P.; Krawczyk, M.; Barman, A. (Appl. Phys. Lett., 2014)

(untitled) - Choudhury, S.; Barman, S.; Otani, Y.; Barman, A. (ACS Nano, 2017)

(untitled) - Mandal, R.; Laha, P.; Das, K.; Saha, S.; Barman, S.; Raychaudhuri, A. K.; Barman, A. (Appl. Phys. Lett., 2013)

(untitled) - Tacchi, S.; Botters, B.; Madami, M.; Kłos, J. W.; Sokolovskyy, M. L.; Krawczyk, M.; Gubbiotti, G.; Carlotti, G.; Adeyeye, A. O.; Neusser, S.; Grundler, D. (Phys. Rev. B, 2012)

(untitled) - Manzin, A.; Bottauscio, O. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Gubbiotti, G.; Tacchi, S.; Madami, M.; Carlotti, G.; Jain, S.; Adeyeye, A. O.; Kostylev, M. P. (Appl. Phys. Lett., 2012)

(untitled) - Choudhury, S.; Saha, S.; Mandal, R.; Barman, S.; Otani, Y.; Barman, A. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Tahir, N.; Zelent, M.; Gieniusz, R.; Krawczyk, M.; Maziewski, A.; Wojciechowski, T.; Ding, J.; Adeyeye, A. O. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Haering, F.; Wiedwald, U.; Nothelfer, S.; Koslowski, B.; Ziemann, P.; Lechner, L.; Wallucks, A.; Lebecki, K.; Nowak, U.; Gräfe, J.; Goering, E.; Schütz, G. (Nanotechnology, 2013)

(untitled) - Manzin, A.; Barrera, G.; Celegato, F.; Coïsson, M.; Tiberto, P. (Sci. Rep., 2016)

(untitled) - Barman, A.; Haldar, A. (Solid State Phys., 2014)

(untitled) - Saha, S.; Barman, S.; Sugimoto, S.; Otani, Y.; Barman, A. (RSC Adv., 2015)

(untitled) - Malinowski, G.; Dalla Longa, F.; Rietjens, J. H. H.; Paluskar, P. V.; Huijink, R.; Swagten, H. J. M.; Koopmans, B. (Nat. Phys., 2008)

(untitled) - Mondal, S.; Choudhury, S.; Barman, S.; Otani, Y.; Barman, A. (RSC Adv., 2016)

OOMMF User’s guide, version1.0, Interagency Report NISTIR 6376 - Donahue, M.; Porter, D. G. (National Institute of Standard and Technology, 1999)

(untitled) - De, A.; Mondal, S.; Banerjee, C.; Chaurasiya, A. K.; Mandal, R.; Otani, Y.; Mitra, R. K.; Barman, A. (J. Phys. D: Appl. Phys., 2017)

Handbook of Magnetic Materials - Buschow, K. H. J. (Elsevier, 2009)

(untitled) - Kumar, D.; Dmytriiev, O.; Ponraj, S.; Barman, A. (J. Phys. D: Appl. Phys., 2012)

LLG Micromagnetics Simulator, developed by M. R. Scheinfein